A Lorentzian decomposition and incremental learning framework for laser-induced breakdown spectroscopy of steels - Panyang Dai; Peichao Zheng; Jingjun Lin; Jinmei Wang; Guanghui Chen; Luning Li (Analytica Chimica Acta, 2026)

Tick-type Schottky contact engineering via Ni-CoOx interlayer for enhanced electron transfer in PEM water electrolyzers - Weiding Wang; Kaini Zhang; Hao Wang; Rui Zhao; Chuanjie Lin; Luning Li; Xinzhe Li; Jinzhan Su; Liejin Guo (Chemical Engineering Journal, 2026)

Sustainability of corrosion-induced degradation of marine engineering structures: A bibliometric analysis based on CiteSpace and VOSviewer (1972-2026) - Zihan Yang; Guangda Yu; Chengyong Li; Bingxuan Zhao; Yansong Liu; Guoqiang Tang; Weihang Yu; Qianhua Liu; Luning Liu; Yu Sun; Yuxin Shi; Zining Li; et al. (Marine Environmental Research, 2026)

Environment-sensitive fluorescent probes targeting mutant IDH1 for in vivo glioma imaging - Wenhua Li; Luning Song; Wenshuo Lv; Tao Xin; Deqing Sun; Wei Zhao (Analytica Chimica Acta, 2026)

Exploring the spatial correlation network and driving factors of adaptability between agricultural new quality productive forces and rural revitalization in China - Yayan Lu; Yingying Jia; Luning Guo; Xinru Chai; Guangchao Li; Xiaoliang Xu (Environment, Development and Sustainability, 2026)

Temperature-driven metagenomics reveals reshaping of microbial communities and nitrogen cycling functions and their potential impacts on Chinese sturgeon host health - Jiachen Zhou; Huifeng Dang; Ye Zhang; Luning Li; Jianan Xu; Houyong Fan; Yueping Zheng; Dan Xu (Aquaculture, 2026)

Integrated multi-omics and physiological analyses reveal mechanism of enhanced gellan gum biosynthesis in an ARTP-induced Sphingomonas paucimobilis mutant - Ling Sun; Shiyi Chen; Yazhen Wang; Lei Sun; Zejian Wang; Yong Zhou; Ali Mohsin; Suyang Li; Luning Zhao; Afira Nayab; Wenjing Sun (Food Microbiology, 2026)

Unraveling synergistic radical and non-radical pathways in bromide and iodide-activated peroxymonosulfate systems for selective abatement of micropollutants - Jiaqi Ren; Ying Huang; Luning Wang; Boyuan Fan; Abdulaziz Al-Anazi; Lecheng Lei; Zhongjian Li (Environmental Research, 2026)

A hybrid assembly mechanism employs nonreducing polyketide synthase-like logic for partially reduced polyketide formation - Xianyan Zhang; Chuanteng Ma; Ziguang Deng; Xingtao Ren; Kaijin Zhang; Wenxue Wang; Luning Zhou; Yongchun Zhu; Guojian Zhang; Qian Che; Tianjiao Zhu; Hongan Long; et al. (Marine Life Science & Technology, 2026)
Fungal iterative type I polyketide synthases (iPKSs) are commonly classified into nonreducing (NR-), partially reducing (PR-), and highly reducing (HR-) polyketide synthases based on their assembly mechanisms and domain structures. These iPKSs have been considered functionally and evolutionarily distinct, characterized by clear boundaries. However, emerging genomic analyses suggest that the diversity of iPKSs in fungi is far from fully understood. Here, we describe the discovery and characterization of PbPKS1 from a marine-derived fungus Penicillium brocae HDN12-143, which exhibits an atypical domain organization arranged as KR-KS-AT-PT-ACP 1 -ACP 2 -CMeT-TE. Heterologous expression of PbPKS1 resulted in the production of two monohydroxybenzoic acids and two pyrones. In vivo and in vitro characterizations demonstrated that PbPKS1 has the capability to synthesize Cα-methylated partially reducing polyketides, yet involved a NR-PKS-like assembly mechanism, featuring a product template (PT) domain for aldol cyclization and a C-terminal thioesterase (TE) domain for product release. Phylogenetic analysis suggests that PbPKS1 belongs to a non-canonical PR-PKS (nPR-PKS) family, which is a minor grouping across the fungal kingdom, and possibly evolved from an NR-PKS through gene recombination. The discovery of nPR-PKS not only expands the diversity of iPKSs but also provides new insights into the evolutionary development of fungal iPKSs.

Novel antifungal talaroenamine L with unusual leptosphaeronyl moiety from marine-derived Talaromyces sp. HDN17-428 via HDACi elicitation - Komal Anjum; Luning Zhou; Khizar Hayyat; Xiaofei Huang; Jiaxiang Wang; Guojian Zhang; Tianjiao Zhu; Qian Che; Dehai Li (Natural Product Research, 2025)

Biodegradable film combined with ploughing: An approach to improve the sustainability of rainfed spring maize production - Rui Qian; Luning Du; Wenjing Li; Wei Wang; Yang Zhang; Yujie Gao; Wenjing Feng; Jiaji Ding; Wenbo Lv; Pengyao Qin; Tie Cai; Xiaolong Ren; et al. (Soil and Tillage Research, 2025)

Influence of genetic variants of imatinib on pharmacokinetics and recurrence-free survival in postoperative patients with gastrointestinal stromal tumor - Luning Sun; Mingqing Xu; Qiang Zhang; Yi Liu; Qiongye Huang; Jianghao Xu; Fengyuan Li; Hao Xu; Yongqing Wang (European Journal of Clinical Pharmacology, 2025)

Biocontrol efficiency and multiple mechanisms of Bacillus velezensis BV07 against postharvest green mold on citrus fruit - Chenyang Zhu; Juanying Huang; Mengyue Wu; GuangHao Li; Xiaoshuang Xia; Luning Zhao; Mahmoud Salah; Xinghua Zhou; Yun Wang (Postharvest Biology and Technology, 2025)

Automatic morphologic classification of Martian craters using imbalanced datasets of Tianwen-1’s MoRIC images with deep neural networks - Qifang Zheng; Rong Huang; Yusheng Xu; Fangzhao Zhang; Changjiang Xiao; Luning Li; Xiaohua Tong (Planetary and Space Science, 2025)

Optimizing zonal management framework suitable for mountain ecosystems by linking landscape, ecosystem service capacities and bundles nested - Yunqi Hao; Yihe Lü; Hui Dang; Da Lü; Chenjun Du; Yi Wang; Luning Wang; Xiaofeng Wang; Xuan Li; Bojie Fu (Journal of Environmental Management, 2025)

Fine mapping of a novel powdery mildew resistance gene PmDM8 derived from a cultivated emmer (Triticum dicoccum) - Yongbo Zhao; Feifei Ma; Junmei Wang; Meng Han; Xuanshuo Liu; Aimen Shafique; Luning Xiao; Xuebing Wang; Jianing Xu; Xingyu Wang; Yueli Bai; Yiming Chai; et al. (Theoretical and Applied Genetics, 2025)

Enhancing H2O2 synthesis in photocatalytic self-Fenton degradation of antibiotics by modulating surface hydrophobicity of Fe-doped g-C3N4 with ionic liquids - Hongjie Zhu; Yushuo Sui; Zirui Yao; Haitao Zhao; Minghui Li; Luning Zou; Yikai Yang; Hongguo Hao; Pengfang Zhang; Hui-Juan Wang; Yao-Yao Wang; Shirong Kang (Journal of Environmental Chemical Engineering, 2025)

Multifunctional dynamic chitosan-guar gum nanocomposite hydrogels in infection and diabetic wound healing - Luning He; Shuyi Xing; Weikang Zhang; Ying Wang; Yian Li; Jinghao Chen; Jinghai Zhang; Siling Wang; Qinfu Zhao (Carbohydrate Polymers, 2025)

New cyclic dipeptide discovered from deep-sea derived Aspergillus sp. HDN20-1401 - Komal Anjum; Xiaofei Huang; Luning Zhou; Tianjiao Zhu; Qian Che; Guojian Zhang; Dehai Li (Natural Product Research, 2024)

Improved nitrogen removal by optimizing the distribution of dissolved oxygen in a simulated constructed wetland system with embedding a water-sealed zone for polishing reclaimed water - Yu Zheng; Nan Zhang; Rongshe Zhang; Chenguang Li; Zhen Liu; Yingzi Guo; Luning Zhang; Qian Wang; Yuanyuan Li; Mohomed Salah; Hao Zheng; Fengmin Li (Journal of Water Process Engineering, 2024)

Refining the final phase of the seafloor spreading process in the West Philippine Basin through the recalibration of magnetic isochrones - Luning Shang; Hailong Li; Kai Lu; Panfeng Li; Gang Hu; Yong Zhang; Yongjian Yao; Chuansheng Yang (Tectonophysics, 2024)

Phase transition behavior and mesophase aging phenomenon during liquid-state carbonization of FCC decant oil - Bin Lou; Jichang Zhang; Jun Li; Weichao Chou; Luning Chai; Lingyan Tian; Xiaofeng Wang; Xiaoqiao Huang; Dong Liu (Fuel, 2024)

New Antibacterial Dihydropyrones Induced by Co-Culture of Penicillium crustosum PRB-2 and Penicillium citrinum HDN11-186 - Guihong Yu; Luning Zhou; Guangwei Wu; Dehai Li (Journal of Ocean University of China, 2024)

Induced seismicity in the Changning salt mining zone, China, could be driven by the pore-pressure diffusion - Haozhe Yang; Rumeng Guo; Guang Zhai; Jiangcun Zhou; Kun Dai; Yong Zheng; Luning Li; Heping Sun (Tectonophysics, 2024)

Speciation and gas-liquid equilibrium study of CO2 absorption in aqueous MEA-DEEA blends - Rui Zhang; Haonan Liu; Ruixi Liu; Yingjie Niu; Luning Yang; Francesco Barzagli; Chao'en Li; Min Xiao (Gas Science and Engineering, 2023)

The association between long-term exposure to outdoor artificial light at night and poor sleep quality among Chinese veterans: A multi-city study - Xinyi Sun; Jiping Tan; Yan Chen; Yuewei Liu; Guang-Hui Dong; Bo-Yi Yang; Nan Li; Luning Wang; Shanshan Li; Gongbo Chen; Yuming Guo (International Journal of Hygiene and Environmental Health, 2023)

Soil fungal taxonomic diversity along an elevation gradient on the semi-arid Xinglong Mountain, Northwest China - Salman Khan; Ning Chen; Cankun Zhang; Luning Wang; Chun Han; Kanglong Lu; Yage Li; Muhammad Rafiq; Awais Iqbal; Changming Zhao (Archives of Microbiology, 2020)

Interaction between serine carboxypeptidase-like protein TtGS5 and Annexin D1 in developing seeds of Triticum timopheevi - Peihong Jiang; JianSheng Gao; Junyi Mu; Luning Duan; Yunsong Gu; Shichen Han; Lin Chen; Yaxuan Li; Yueming Yan; Xiaohui Li (Journal of Applied Genetics, 2020)

Analyzing the action of evolutionarily conserved modules on HMW-GS 1Ax1 promoter activity - Luning Duan; Shichen Han; Ke Wang; Peihong Jiang; Yunsong Gu; Lin Chen; Junyi Mu; Xingguo Ye; Yaxuan Li; Yueming Yan; Xiaohui Li (Plant Molecular Biology, 2020)

Genome-wide identification of internal reference genes for normalization of gene expression values during endosperm development in wheat - Junyi Mu; Lin Chen; Yunsong Gu; Luning Duan; Shichen Han; Yaxuan Li; Yueming Yan; Xiaohui Li (Journal of Applied Genetics, 2019)

Microbial degradation of organophosphorus pesticides: novel degraders, kinetics, functional genes, and genotoxicity assessment - Bo Jiang; Nana Zhang; Yi Xing; Luning Lian; Yating Chen; Dayi Zhang; Guanghe Li; Guangdong Sun; Yizhi Song (Environmental Science and Pollution Research, 2019)

Arsenic Trioxide and Icariin Show Synergistic Anti-leukemic Activity - Zhi Wang; Hong Zhang; Liling Dai; Tongguo Song; Ping Li; Yali Liu; Luning Wang (Cell Biochemistry and Biophysics, 2015)

A mismatch process in brief delayed matching-to-sample task: an fMRI study - Xi Zhang; Lin Ma; Shunwei Li; Yuping Wang; Xuchu Weng; Luning Wang (Experimental Brain Research, 2008)

Distinctive conflict processes associated with different stimulus presentation patterns: an event-related potential study - Xi Zhang; Yuping Wang; Shunwei Li; Luning Wang; Shujuan Tian (Experimental Brain Research, 2005)

D-Galactose-caused life shortening in Drosophila melanogaster and Musca domestica is associated with oxidative stress - Xu Cui; Luning Wang; Pingping Zuo; Zhitao Han; Zhengyu Fang; Wenbin Li; Jiankang Liu (Biogerontology, 2004)